Business Transformation in Industry 4.0 and Strategies for Facing Industry in the 5.0 Era - Rio Afrianda; Veithzal Rivai Zainal; Indra Siswanti (Universitas Mercu Buana, 2023)
The purpose of this study is to confirm or refute whether companies are ready for the next industrial revolution. Current market conditions show that businesses are still struggling to digitize their business through the integration of Internet of Things (IoT), artificial intelligence (AI), cloud technology, and advanced technologies. other. This study uses an approach that integrates human labor in collaboration with automated processes in the supply chain. The results of this study that analyzes and evaluates the impact of Industry 5.0 on entrepreneurs where Industry 4.0 Analysis provides results based on interviews with practicing sales representatives as well. It focuses on the business landscape and its aim is to identify existing gaps, opportunities and threats. This analysis also describes the best path to transformation in the next industrial revolution.